리튬 또는 발프로산으로 치료받은 양극성장애 환자의 무증상 갑상선저하증 - 최현만; 장재승; 김자연; 김정현; 최정은; 하태현; 하규섭; Choi, Hyeon Man; Chang, Jae Seung; Kim, Jayoun; Kim, Jeong Hyun; Choi, Jung Eun; et al. (Journal of the Korean Society of Biological Psychiatry, 2013)
Objectives To investigate the pattern of subclinical hypothyroidism (SCH) in patients with bipolar disorders managed by lithium or valproic acid. Methods The study participants were 106 patients with DSM-IV bipolar disorders receiving planned maintenance treatment at the Mood Disorders Clinic of Seoul National University Bundang Hospital (aged between 17 and 64, mean duration of follow-up = 875.65 days). Using the bipolar disorder registry, thyroid function data were analyzed to assess the frequency of and the risk factors for SCH in patients managed by lithium (n = 64) or valproic acid (n = 42) for more than 5 months. Results Overall frequencies of SCH were 20.3% (13/64) in the lithium group, 14.3% (6/42) in the valproic acid group, and between the two groups there is no difference (p = 0.43). No differences were observed in the potential risk factors for SCH between the two groups including age, sex, subtype of bipolar disorder, baseline TSH, and concomitant antipsychotic use. In cases with SCH, thyroid-stimulating hormone (TSH) showed a tendency to increase at 3 month after the initiation of lithium or valproic acid. A gradual increase in the number of patients showing SCH was found within the first 3 years of medication. Conclusions With regular monitoring and careful assessment, there was no difference in the risk of SCH between lithium and valproic acid maintenance. The risk of mood stabilizer-associated SCH may gradually increase within 3 years following the commencement of medication, thereby mandating close monitoring for the first 3 years of treatment. Further studies with large sample size would be needed to confirm these findings.